Why do families still not receive the child support grant in South Africa? A longitudinal analysis of a cohort of families across South Africa - Zembe-Mkabile Wanga; Doherty Tanya; Sanders David; Jackson Debra; Chopra Mickey; Swanevelder Sonja; Lombard Carl; Surender Rebecca (BMC, 2012)
Abstract Background Child cash transfers are increasingly recognised for their potential to reduce poverty and improve health outcomes. South Africa's child support grant (CSG) constitutes the largest cash transfer in the continent. No studies have been conducted to look at factors associated with successful receipt of the CSG. This paper reports findings on factors associated with CSG receipt in three settings in South Africa (Paarl in the Western Cape Province, and Umlazi and Rietvlei in KwaZulu-Natal). Methods This study used longitudinal data from a community-based cluster-randomized trial (PROMISE EBF) promoting exclusive breastfeeding by peer-counsellors in South Africa (ClinicalTrials.gov: NCT00397150). 1148 mother-infant pairs were enrolled in the study and data on the CSG were collected at infant age 6, 12, 24 weeks and 18-24 months. A stratified cox proportional hazards regression model was fitted to the data to investigate factors associated with CSG receipt. Results Uptake of the CSG amongst eligible children at a median age of 22 months was 62% in Paarl, 64% in Rietvlei and 60% in Umlazi. Possessing a birth certificate was found to be the strongest predictor of CSG receipt (HR 3.1, 95% CI: 2.4 -4.1). Other factors also found to be independently associated with CSG receipt were an HIV-positive mother (HR 1.2, 95% CI: 1.0-1.4) and a household income below R1100 (HR1.7, 95% CI: 1.1 -2.6). Conclusion Receipt of the CSG was sub optimal amongst eligible children showing administrative requirements such as possessing a birth certificate to be a serious barrier to access. In the spirit of promoting and protecting children's rights, more efforts are needed to improve and ease access to this cash transfer program.